2022
DOI: 10.23736/s0026-4806.21.07207-4
|View full text |Cite
|
Sign up to set email alerts
|

The clock diet: a practical nutritional guide to manage obesity through chrononutrition

Abstract: Editorial Board Member comments Dear authors, an editorial board member has reviewed your work that has been found interesting. Some minor changes are requestes. Best regards In this review the authors discuss A PRACTICAL NUTRITIONAL GUIDE TO MANAGE OBESITY THROUGH CHRONONUTRITION. The authors discuss extensivley chronobiology and chrononutrition and their role in obesity.We are very grateful to the Editorial Board Member for his/her appreciation of our findings and his/her most positive report. We are hopeful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 101 publications
0
14
0
8
Order By: Relevance
“…Since it has been reported that postmenopausal women with an evening chronotype, escaping the "physiological" propensity for a morning chronotype, have higher health risks, such as more obesity or cardiometabolic diseases [46,81], new nutritional approaches that correct circadian alterations should be developed. Chrononutrition is a new area of research that investigates the effects of diet (particularly timing and nutrients) on CR [19]. In this context, foods and macronutrients at specific times of day have been shown to influence circadian oscillations in clock genes [19].…”
Section: Nutritional Approach To Women With Menopause and Obesity And...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since it has been reported that postmenopausal women with an evening chronotype, escaping the "physiological" propensity for a morning chronotype, have higher health risks, such as more obesity or cardiometabolic diseases [46,81], new nutritional approaches that correct circadian alterations should be developed. Chrononutrition is a new area of research that investigates the effects of diet (particularly timing and nutrients) on CR [19]. In this context, foods and macronutrients at specific times of day have been shown to influence circadian oscillations in clock genes [19].…”
Section: Nutritional Approach To Women With Menopause and Obesity And...mentioning
confidence: 99%
“…Chrononutrition is a new area of research that investigates the effects of diet (particularly timing and nutrients) on CR [19]. In this context, foods and macronutrients at specific times of day have been shown to influence circadian oscillations in clock genes [19]. For instance, it has also been documented that the fat consumed can influence the genes involved in the CR through epigenetic modifications [82].…”
Section: Nutritional Approach To Women With Menopause and Obesity And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the circadian rhythmicity associated with carbohydrate metabolism and insulin sensitivity peaks in the morning and progressively declines towards the night, [45] it has been well-established that a higher proportion of daily carbohydrates should be consumed earlier in the day, while avoiding highcarbohydrate dinners to optimize glycemic control. [7,46] Besides assessing the quantity and distribution of carbohydrates, the quality-specifically the glycemic index (GI) of carbohydrates have also been evaluated in alignment with metabolic circadian patterns. Evidence suggest that the time of day may confound and/or supersede the impact of GI on overall glucose homeostasis throughout the day, whereby for the same carbohydrate amount and/or GI, the morning postprandial glycemic response is generally lower than that of the evening.…”
Section: Carbohydratesmentioning
confidence: 99%
“…[ 102 ] Evidence have highlighted the circadian oscillatory nature of intestinal receptors modulating glucose absorption, such as the sodium/glucose cotransporter (SGLT1) and glucose transporter 2 (GLUT2), governed by clock genes. [ 46 ] These in turn exhibits circadian rhythms in the absorptivity of various nutrients in line with fasting–feeding cycles. [ 4 ] Therefore, these present potential targets for identifying optimal timing of the intakes of polyphenols such as catechins, which have also been independently reported to inhibit SGLT1 and GLUT2.…”
Section: Dietary Components Intake Timing and Their Interaction With ...mentioning
confidence: 99%